Moral markets : the critical role of values in the economy - Zak, Paul J. (Princeton : Princeton University Press)
Drawing on converging evidence from neuroscience, social science, biology, law, and philosophy, Moral Markets makes the case that modern market exchange works only because most people, most of the time, act virtuously. --from publisher description